Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1074/jbc.m600579200
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Smad3 and CREB-1 in Mediating Transforming Growth Factor-β (TGFβ) Induction of TGFβ3 Secretion

Abstract: Because increased transforming growth factor-␤ (TGF␤) production by tumor cells contributes to cancer progression through paracrine mechanisms, identification of critical points that can be targeted to block TGF␤ production is important. Previous studies have identified the precise signaling components and promoter elements required for TGF␤ induction of TGF␤1 expression in epithelial cells (Yue, J., and Mulder, K. M. (2000) J. Biol. Chem. 275, 30765-30773). To determine how regulation of TGF␤3 expression diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 61 publications
2
43
0
Order By: Relevance
“…Although MDCK cells stably overexpressing Pez express significantly elevated transcript levels of all three TGFβ isoforms (TGFβ 1 , TGFβ 2 and TGFβ 3 ), 10 it is well documented that TGFβ signaling can autoinduce transcription of its own mRNA, [39][40][41][42] and we have observed this to be the case in the MDCK cell culture model used in our studies (Wyatt L and Khew-Goodall Y, unpublished observations). The increase in TGFβ transcript levels detected following stable overexpression of Pez may therefore be due either to a direct effect of Pez on TGFβ transcription, or the auto-induction of TGFβ transcription down-stream of TGFβ-mediated signal transduction.…”
Section: Molecular Mechanism Of Pez-mediated Tgfβ Signalingsupporting
confidence: 49%
“…Although MDCK cells stably overexpressing Pez express significantly elevated transcript levels of all three TGFβ isoforms (TGFβ 1 , TGFβ 2 and TGFβ 3 ), 10 it is well documented that TGFβ signaling can autoinduce transcription of its own mRNA, [39][40][41][42] and we have observed this to be the case in the MDCK cell culture model used in our studies (Wyatt L and Khew-Goodall Y, unpublished observations). The increase in TGFβ transcript levels detected following stable overexpression of Pez may therefore be due either to a direct effect of Pez on TGFβ transcription, or the auto-induction of TGFβ transcription down-stream of TGFβ-mediated signal transduction.…”
Section: Molecular Mechanism Of Pez-mediated Tgfβ Signalingsupporting
confidence: 49%
“…3A ). CREB1 has been shown to interact and cooperate with SMADs in the transcriptional activation of certain genes ( 30,31 ). This suggested that CREB1 cooperates with SMADs to activate TGFB2 gene transcription.…”
Section: Creb1 Regulates the Induction Of Tgfb2 By Tgfbmentioning
confidence: 99%
“…CREB factors promote tumorigenesis in many cancers, including non-small cell lung carcinoma, acute myelogenous leukemia, and glioma ( 19 , 23-27 ). Interestingly, the CREB/ATF family of transcription factors has been shown to regulate and cooperate with SMADs in the transcriptional regulation of multiple genes (28)(29)(30)(31).…”
Section: Research Articlementioning
confidence: 99%
“…4A) and activate CREB-dependent gene expression (30,31). Because the promoter of both TGF-b2 (32) and -b3 (33,34) contains cAMP response element, we decided to investigate whether selective inhibition of p38 MAPKs by SB203580 (10 mM) could interfere with the mTNF-a-induced TGF-b production. As seen in Fig.…”
Section: Mtnf-a Signaling Induces the Mkk4 Signaling Pathwaymentioning
confidence: 99%